THE CULTURAL INDUSTRIES DES/RE/CONSTRUCTION OF STEREOTYPES FAMILIES IN TRAINING CONCEPTS TEACHERS - Oliveira Junior, Isaias Batista de [UNESP]; Foletto de Moraes, Dirce Aparecida; Coimbra, Renata Maria [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
Conceptualizing family in contemporary society is an exercise that requires deep reflection, as the cultural industry through the media sprays and brings up a series of biographical experiences and organizational models that contribute to deepen and broaden the stigmata reinforcing stereotypes. Thinking about the family concept of questioning we aim of this study to understand how the cultural industry contributes to the family of concept formation in view of pedagogy students in the program as a condition of their future professional activities. Students of the first year of the mentioned course of a Public University of the State of Parana participated in the research, through debates about the concept of family using as strategies texts, sources available in the Internet and in television advertisements. We conclude that the research subjects view points to a classic vision of family, based on defining characteristics. It is necessary to question the reality of families in contemporary times in the training process of these individuals and the complexity of the factors that interfere with its concept of the family, therefore, it must be understood historically and analyzed in their specificity by adopting certain pedagogical assumptions.
Keywords: School; Media; Concepts; Families